Incidental Prostate Cancer in Transurethral Resection of the Prostate Specimens in the Modern Era. (29th April 2014) - Otto, Brandon; Barbieri, Christopher; Lee, Richard; Te, Alexis E.; Kaplan, Steven A.; Robinson, Brian; Chughtai, Bilal
Abstract : Objectives. To identify rates of incidentally detected prostate cancer in patients undergoing surgical management of benign prostatic hyperplasia (BPH). Materials and Methods. A retrospective review was performed on all transurethral resections of the prostate (TURP) regardless of technique from 2006 to 2011 at a single tertiary care institution. 793 men (ages 45–90) were identified by pathology specimen. Those with a known diagnosis of prostate cancer prior to TURP were excluded (n = 22 ) from the analysis. Results. 760 patients had benign pathology; eleven (1.4%) patients were found to have prostate cancer. Grade of disease ranged from Gleason3 + 3 = 6 to Gleason3 + 4 = 7 . Nine patients had cT1a disease and two had cT1b disease. Seven patients were managed by active surveillance with no further events, one patient underwent radiation, and three patients underwent radical prostatectomy. Conclusions. Our series demonstrates that 1.4% of patients were found to have prostate cancer, of these 0.5% required treatment. Given the low incidental prostate cancer detection rate, the value of pathologic review of TURP specimens may be limited depending on the patient population.